2006
DOI: 10.1590/s0102-86502006000900011
|View full text |Cite
|
Sign up to set email alerts
|

Análise da cicatrização na Linha Alba com uso de extrato aquoso de Orbignya phalerata (babaçu): estudo controlado em ratos

Abstract: RESUMOIntrodução: O mesocarpo do babaçu (Orbignya phalerata) tem sido utilizado em estudos experimentais para verificar a sua ação antiinflamatória. No Maranhão, é muito utilizado como alimento e como remédio popular para cicatrização de ferimentos. Objetivo -Avaliar macroscópica, histológica e tensiometricamente, a ação do extrato de Orbygnia phalerata no processo de cicatrização de laparotomias medianas em ratos. Métodos: Quarenta ratos da linhagem Wistar, adultos, machos, foram utilizados em procedimento ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Recent research has analyzed other applications of the outer layers of the babassu, including the anti-inflammatory and analgesic properties [26][27][28][29] of the mesocarp, which is also capable of adsorbing various textile industry dyes. 30 Also, the structural features associated with mesocarp and epicarp permit their use as polymeric supports for the immobilization of ethylenesulfide followed by divalent cation removal from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has analyzed other applications of the outer layers of the babassu, including the anti-inflammatory and analgesic properties [26][27][28][29] of the mesocarp, which is also capable of adsorbing various textile industry dyes. 30 Also, the structural features associated with mesocarp and epicarp permit their use as polymeric supports for the immobilization of ethylenesulfide followed by divalent cation removal from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-ulcer activity of several chemical compounds isolated from plants has been determined. In Brazil, several plant extracts are used in popular medicine for the treatment of digestive disorders, including gastric ulcers 4 , 5 , 7 , 8 , 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors such as increased vascular permeability, intestinal motility, vagal activity, decreased gastric blood flow and prostaglandin levels play an important role in the pathogenesis of gastric ulcers. Thus, several experimental models can be used in an attempt to elucidate the mechanism of action of plant extracts 4 , 5 , 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed a potential healing effect based on the animals treated with the extract, which had better results for the tensiometric parameter and more excellent resistance. 84 Under the same conditions, an aqueous extract of babassu mesocarp induced better healing of surgical injuries of the bladder. 85 An apparent circular incision of 2 cm in diameter with a metallic puncture was made in mice.…”
Section: Antimicrobial and Wound Healing Potential Of Babassu Coconut...mentioning
confidence: 95%